2022
DOI: 10.1111/ijd.16107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, histology, and treatment outcomes of granular parakeratosis: a systematic review

Abstract: Background Granular parakeratosis is a rare disorder characterized by erythematousbrown hyperkeratotic papules and erythematous patches with scaling, occurring predominantly in the flexures and sites of occlusion. While the exact underlying pathogenesis remains unknown, there has been a wide variety of precipitating factors and treatment options reported in the literature.Objective We systematically reviewed and identified precipitants of granular parakeratosis, as well as its clinical and histologic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Granular parakeratosis is often triggered by exposure to a number of topical agents, including zinc oxide, antiperspirants and benzalkonium chlorides (BACs), but may also arise without an identified trigger. 3 There was no history of zinc oxide or antiperspirant use to the groin area in this patient, but it was revealed that her clothing was being washed using laundry products containing BACs.…”
Section: Answermentioning
confidence: 78%
“…Granular parakeratosis is often triggered by exposure to a number of topical agents, including zinc oxide, antiperspirants and benzalkonium chlorides (BACs), but may also arise without an identified trigger. 3 There was no history of zinc oxide or antiperspirant use to the groin area in this patient, but it was revealed that her clothing was being washed using laundry products containing BACs.…”
Section: Answermentioning
confidence: 78%
“…A systematic review of GP cases found that 43.4% reported topical products as an etiologic factor, most commonly zinc oxide, deodorants/antiperspirants, and benzalkonium chloride-containing products. 1 However, cases have also been reported in the absence of topical exposures, particularly in association with occlusive environments imposed by diapers, sweating, and obesity . One case of congenital GP has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…GP can be self-limiting, although recent systematic review found that spontaneous clearing has only been reported in a minority (4.7%) of cases. 1 Elimination of causative agents is generally considered the first line in management in cases where a trigger is identified, but a variety of additional topical and systemic agents have also been used with variable outcomes. In this case, discontinuation of topical zinc oxide along with application of petroleum jelly for skin barrier protection and short courses of topical steroids (hydrocortisone 2.5% ointment in the inguinal region and triamcinolone 0.1% ointment in the perianal region) led to complete resolution.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of recognition of anatomical distribution, the naming has also evolved. 4 In 1998, Mehregan et al 5 reported a case involving the groin as intertriginous GP, omitting the word “axillary”. In 1999, Metze et al 6 renamed it GP, acknowledging involvement in non-intertriginous areas and omitting the word “intertriginous”.…”
Section: Discussionmentioning
confidence: 99%
“…Two main lesions types of GP were reported, including erythematous scales and papules (plaques). 4 The first feature of GP is erythematous scales manifested as symmetrical erythema with pathognomonic multi-layer brown epidermal scales. Kumarasinghe et al first proposed the term hyperkeratotic flexural erythema as a better description for this type.…”
Section: Discussionmentioning
confidence: 99%